2014
DOI: 10.1016/j.heares.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 26 null mice exhibit spiral ganglion degeneration that can be blocked by BDNF gene therapy

Abstract: Mutations in the connexin 26 gene (GJB2) are the most common genetic cause of deafness, leading to congenital bilateral non-syndromic sensorineural hearing loss. Here we report the generation of a mouse model for a connexin 26 (C×26) mutation, in which cre-Sox10 drives excision of the C×26 gene from non-sensory cells flanking the auditory epithelium. We determined that these conditional knockout mice, designated Gjb2-CKO, have a severe hearing loss. Immunocytochemistry of the auditory epithelium confirmed abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 68 publications
1
34
0
Order By: Relevance
“…The severe cochlear pathology and hearing deficits in the Gjb2 -CKO mouse studied here have been previously documented (Takada et al, 2014). Other mouse models with Cx26 mutations have also revealed severe cochlear dysfunction and pathologies (Cohen-Salmon et al, 2002; Kudo et al, 2003; Sun et al, 2009).…”
Section: Discussionsupporting
confidence: 53%
“…The severe cochlear pathology and hearing deficits in the Gjb2 -CKO mouse studied here have been previously documented (Takada et al, 2014). Other mouse models with Cx26 mutations have also revealed severe cochlear dysfunction and pathologies (Cohen-Salmon et al, 2002; Kudo et al, 2003; Sun et al, 2009).…”
Section: Discussionsupporting
confidence: 53%
“…In accordance with this possibility, mutations in the connexin 26 (Cx26) gene (GJB2 mutations), which forms gap junctions between SCs (48, 49), causes deafness. Mice with Cx26 loss show HC loss only after the onset of hearing (50,51), providing evidence that SCs are key regulators of homeostasis during sensory processing in the functional organ of Corti. We also found that HCs must be present in the neonatal organ of Corti for IBC/ IPhC replacement to occur after ablation.…”
Section: Discussionmentioning
confidence: 98%
“…We determined the thresholds in the left ear of each animal with auditory brainstem response (ABR) measurements, as described in detail previously (Takada et al, 2014). ABRs were measured at 8, 20, and 32 kHz at least 1 day prior to DT injection or noise exposure (baseline ABRs) and then again 1 month later (N = 5 WT and DT 1M, and N = 9 for Noise group).…”
Section: Methodsmentioning
confidence: 99%